2006
DOI: 10.1149/1.2142209
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Anisotropy in the Anodic Dissolution of Silicon

Abstract: We report on an in situ, real-time, electrochemical, polarized, attenuated total reflection Fourier transform infrared spectroscopic investigation of Si(100), (111), and (110) surfaces in diluted HF solution ( cnormalF=0.05M , pH 3). Prior to the IR measurements, cyclic voltammetry was carried out on the samples in a standard three-electrode arrangement, then IR spectra were recorded as a function of potential using 50-mV potential increments. The results give evidence for potential-induced absorption changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…It is plausible that the surface crystallography (Si-Si distance and bond angles) induces a different SiOH to SiOSi ratio at the (1 0 0) and the (1 1 1) surface, leading to a different dissolution rate. A more thorough analysis of these effects, including data obtained on other orientations and a kinetic model of Si dissolution in this regime, are presently in progress and will be fully developed elsewhere [26].…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that the surface crystallography (Si-Si distance and bond angles) induces a different SiOH to SiOSi ratio at the (1 0 0) and the (1 1 1) surface, leading to a different dissolution rate. A more thorough analysis of these effects, including data obtained on other orientations and a kinetic model of Si dissolution in this regime, are presently in progress and will be fully developed elsewhere [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SERS studies [22] showed that in addition to Si-H bonds, Si-O and Si-OH ones are also formed on the the surface of silicon during anisotropic etching [23] showed that while the surface of Si electrode is free from oxides in the cathodic range of potentials, i.e., at E < E OCP ≈ −0.97 V (Ag/AgCl in 40% NH 4 F, pH 8), a thin layer of oxides (1.0 -1.5 mono-layer) is already present on the surface within the double layer region, whereas in the range of anisotropic anodic etching (E > 0 V (Ag/AgCl)) the amount of oxygen on Si surface increases several times. Thus the above described data show that anodic oxidation of Si proceeds via formation of silicon oxygen species on the electrode surface, i.e.…”
Section: Theoretical Background For Analysis Of Experimental Datamentioning
confidence: 99%
“…oxide"/hydroxide film (95), the current is slightly orientation dependent (50,96,97), and the surface recombination velocity is high (98). In this region, the surface remains rather rough on the nanometric scale (99).…”
Section: Silicon In Fluoride Electrolytesmentioning
confidence: 99%